Factors Affecting Continuance Intention Towards Adoption of Linkaja Mobile Payment - Hafizh, Muhammad Damar; Arif Imam Suroso; Ratono, Joko (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: Technological developments make all activities easy, practical, and efficient, one of which occurs in instruments and payment systems that can be accessed mobile using a smartphone. LinkAja is one of the many mobile payment services in IndonesiaPurpose: This study examines the factors in the modified UTAUT2 model and factors affecting continuance intention in using LinkAja. Design/methodology/approach: The research analyzes the impact of factors within the modified UTAUT2 model on influencing continuance intention in using LinkAja, understanding respondent characteristics, and formulating managerial implications to enhance the continued use of LinkAja. The study involved 200 respondents who have used LinkAja, selected through purposive sampling. Data were collected through online questionnaires, and the analysis was conducted using Covariance-based Structural Equation Modeling (CB-SEM).Findings/Result: The results of this research reveal that time savings, user-friendliness, the influence of individuals' highly valued smartphone ownership, enthusiasm, cost savings, routines, and habits are crucial factors identified in the modified UTAUT2 model. Continuing to use LinkAja over alternatives is the key to continuance intention in using LinkAja. Performance expectancy, hedonic motivation, and habit significantly affect continuance intention in using LinkAja.Conclusion: This study identifies key factors from the modified UTAUT2 model that significantly affect the continuance intention of using LinkAja, such as performance expectancy, hedonic motivation, and habit. Managerial implications suggest that enhancing application reliability, introducing innovative features, and forming strategic partnerships can promote continued use of LinkAja.Originality/value (State of the art): This research uniquely applies a modified UTAUT2 model to mobile payments in Indonesia, identifying critical factors influencing the continued use of LinkAja. It enriches academic understanding and offers practical strategies for improving mobile payment systems. Keywords: CB SEM, Continuance Intention, LinkAja, Mobile Payment, UTAUT2